PREDIKSI PRODUK PENJUALAN DI SUPERMARKET DENGAN METODE ALGORITMA K-NEAREST NEIGHBORS (KNN) - Ahmad Muflih Wafir; Zaehol Fatah (CV. ALIM'SPUBLISHING, 2025)
In today's era, there are already many companies that have been established, from urban to rural areas, various companies have been established, especially companies that provide daily necessities such as supermarkets. And each company competes with each other in selling its products with the expected results. In this study, researchers use data to support this study. Because sales of goods or product stock can be calculated in sales results, the higher the sales, the higher the risk that will be faced. This study aims to apply data mining in analyzing sales results that occur in supermarkets. And to find out its impact on sales. This researcher uses the KNN method, by looking for test results with this method which will be implemented using the Rapid Miner application which will later produce the results of its analysis.